Formation and HPLC Analysis of the Natural Lake Pigments Obtained from Weld (Reseda luteola L.) - KARADAG , RECEP; CUCEN , EKREM; YILDIZ , YUSUF (Asian Journal of Chemistry, 2011)
In this work, the weld lake pigments, aluminium-weld and tin-weld were obtained by the reaction of KAl(SO4)2.12H2O and SnCl2.2H2O solutions with weld. The high performance liquid chromatography (HPLC) with diode-array detection method was utilized for the identification of the lake pigments. Reversed-phase HPLC with diode-array UV-VIS spectrophotometric detection has been used in this identification. The extraction of dyestuffs from the lake pigments were carried out with HCl/methanol /water (2:1:1; v/v/v) solution. From the results of the HPLC analysis of the weld lake pigments, it was determined that the luteolin and apigenin present in the lake pigments was precipitated by Al(III) and Sn(II).